Usability Audit Model for Tourism Destination Websites. - Alba-Muñoz, Simón; Rojas-de-Gracia, María Mercedes; Sierra-Herrezuelo, Plácido (IGI Global, 2020)
In a globalized world, tourist destinations must have a website containing accurate information for potential tourists. However, there is currently no model that serves as a guide to evaluate the usability of tourism websites. A web usability audit manual is presented in this work with the application of a case study methodology, which combines theoretical contributions with those of a real audit of a tourism institution. Apart from the description of the manual itself, the results of this work have made it possible to identify a series of actions to be taken into account, as well as others that should be avoided when a usability audit is being carried out in the tourism field.
https://www.igi-global.com/about/rights-permissions/content-reuse/
Keywords: Turismo; Páginas Web; Usability; Audit; Tourism; Destination websites